Simultaneous Ring Voice-over-Internet Phone System Enables Rapid Physician Elicitation of Explicit Informed Consent in Prehospital Stroke Treatment Trials - Sanossian, Nerses (S. Karger AG, 2009)
BACKGROUND: Cellular phone conversations between on-scene patients or their legally authorized representatives (LARs) and off-scene enrolling physician-investigators require immediate and reliable connection systems to obtain explicit informed research consent in prehospital treatment trials. METHODS: The NIH Field Administration of Stroke Therapy – Magnesium (FAST-MAG) Trial implemented a voice-over-internet protocol (VOIP) simultaneous ring system (multiple investigator cell phones called simultaneously and first responder connected to call) to enable physician-investigators to elicit consent immediately from competent patients or LARs encountered by 228 ambulances enrolling patients in a multicenter prehospital stroke trial. For 1 month, the number, origin, duration, and yield of enrolling line calls were monitored prospectively. RESULTS: Six investigators were connected to 106 enrolling line calls, with no identified unanswered calls. Thirty-five percent of new patient calls yielded an enrollment. The most common reasons for non-enrollment were last known well >2 h (n = 7) and uncon sentable patient without LAR available (n = 7). No non-enrollments were directly attributable to the VOIP system. In enrollments, consent was provided by the patient in 67% and a LAR in 33%. The duration of enrollment calls (mean ± SD: 8.4 ± 2.5 min, range 6–14) was longer than non-enrollment calls (5.5 ± 3.5, range 2–13; p < 0.001). The median interval from last known well to study agent start was 46 min, and 70% were enrolled within 60 min of onset. CONCLUSIONS: The simultaneous ring system was reliable and effective, permitting enrollment of a substantial number of patients within the first hour after stroke onset. VOIP cellular networks with simultaneous ring are a preferred means of facilitating consent in prehospital treatment trials.